Enriching Wheat Bread With Banana Peel Powder: Impact on Nutritional Attributes, Bioactive Compounds, and Antioxidant Activity - Most. Jesmin Akhter; Md. Al-Amin; Md Akram Hossain; Md. Murtuza Kamal (International Journal of Food Science)
This research investigated the impact of enriching bread with banana peel powder (BPP) on nutritional attributes, bioactive components, antioxidant activity, and sensory characteristics. Four bread samples were prepared and evaluated: S1 (control), S2 (5% BPP), S3 (7% BPP), and S4 (10% BPP). The addition of BPP resulted in a reduction in moisture content and an increase in ash, fat, protein, and fibre levels, while reducing overall carbohydrate content. Furthermore, BPP-enriched bread exhibited an increase in total phenolic content (TPC) (ranging from 28.46 to 42.38 mg GAE/100 g) and total flavonoid content (TFC) (ranging from 6.63 to 9.46 QE mg/g), indicating enhanced antioxidant properties. The DPPH assay demonstrated the antioxidant potential of BPP-incorporated bread, with the radical scavenging activity (RSA) increasing from 18.84% to 53.03% with increasing BPP enrichment. Color assessment revealed changes in both crust and crumb, with a decrease from 78.46 to 40.53 in the lightness (L∗) value of the crust and from 61.21 to 41.10 in the lightness (L∗) value of the crumb. Additionally, changes in a∗ and b∗ values were observed. The a∗ values varied between 17.59 and 12.42 for the crust and between 6.96 and 5.89 for the crumb. The b∗ values varied between 31.61 and 23.65 for the crust and between 19.63 and 16.58 for the crumb. Sensory evaluation suggested that up to 5% BPP inclusion in bread mirrored the texture, taste, appearance, and overall acceptability of control bread, but enrichment beyond 5% resulted in lower sensory scores. In summary, the incorporation of BPP significantly influenced various aspects of bread, highlighting its potential for applications in the food and industry sectors.